2022
DOI: 10.1007/s13311-022-01299-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose 7,8-Dihydroxyflavone Administration After Status Epilepticus Prevents Epilepsy Development

Abstract: Temporal lobe epilepsy often manifests months or even years after an initial epileptogenic insult (e.g., stroke, trauma, status epilepticus) and, therefore, may be preventable. However, no such preventive treatment is currently available. Aim of this study was to test an antioxidant agent, 7,8-dihydroxyflavone (7,8-DHF), that is well tolerated and effective in preclinical models of many neurological disorders, as an anti-epileptogenic drug. However, 7,8-DHF also acts as a TrkB receptor agonist and, based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The discovery of 7,8-DHF as a direct PDXP inhibitor was unexpected. Interestingly, numerous in vivo studies have reported the effectiveness of 7,8-DHF in brain disorder models, including rodent models of Alzheimer’s disease ( Zhang et al, 2014a ; Devi and Ohno, 2012 ; Bollen et al, 2013 ; Castello et al, 2014 ; Aytan et al, 2018 ; Gao et al, 2016 ; Akhtar et al, 2021 ; Hsiao et al, 2014 ), depression ( Blugeot et al, 2011 ; Zhang et al, 2014b ; Yao et al, 2016 ; Zhang et al, 2016 ; Li et al, 2022 ; Amin et al, 2020 ), schizophrenia ( Jaehne et al, 2021 ; Han et al, 2016 ; Yang et al, 2014 ; Han et al, 2017 ; Ren et al, 2013 ), epilepsy ( Becker et al, 2015 ; Guarino et al, 2022 ), and autism ( Johnson et al, 2012 ; Kang et al, 2017 ; Lee and Han, 2019 ; Chen et al, 2023 ). Although PLP deficiency is thought to contribute to the respective human conditions ( di Salvo et al, 2012 ; Majewski et al, 2016 ; Sorolla et al, 2016 ), PLP-dependent processes have not yet been considered in the context of 7,8-DHF-induced effects.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of 7,8-DHF as a direct PDXP inhibitor was unexpected. Interestingly, numerous in vivo studies have reported the effectiveness of 7,8-DHF in brain disorder models, including rodent models of Alzheimer’s disease ( Zhang et al, 2014a ; Devi and Ohno, 2012 ; Bollen et al, 2013 ; Castello et al, 2014 ; Aytan et al, 2018 ; Gao et al, 2016 ; Akhtar et al, 2021 ; Hsiao et al, 2014 ), depression ( Blugeot et al, 2011 ; Zhang et al, 2014b ; Yao et al, 2016 ; Zhang et al, 2016 ; Li et al, 2022 ; Amin et al, 2020 ), schizophrenia ( Jaehne et al, 2021 ; Han et al, 2016 ; Yang et al, 2014 ; Han et al, 2017 ; Ren et al, 2013 ), epilepsy ( Becker et al, 2015 ; Guarino et al, 2022 ), and autism ( Johnson et al, 2012 ; Kang et al, 2017 ; Lee and Han, 2019 ; Chen et al, 2023 ). Although PLP deficiency is thought to contribute to the respective human conditions ( di Salvo et al, 2012 ; Majewski et al, 2016 ; Sorolla et al, 2016 ), PLP-dependent processes have not yet been considered in the context of 7,8-DHF-induced effects.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of 7,8-DHF as a direct PDXP inhibitor was unexpected. Interestingly, numerous in vivo studies have reported the effectiveness of 7,8-DHF in brain disorder models, including rodent models of Alzheimer's disease (49)(50)(51)(52)(53)(54)(55)(56), depression (57)(58)(59)(60)(61)(62), schizophrenia (63)(64)(65)(66)(67), or epilepsy (68,69), as well as in rodent models of autism (70)(71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of 7,8-DHF as a direct PDXP inhibitor was unexpected. Interestingly, numerous in vivo studies have reported the effectiveness of 7,8-DHF in brain disorder models, including rodent models of Alzheimer's disease (50)(51)(52)(53)(54)(55)(56)(57), depression (58)(59)(60)(61)(62)(63), schizophrenia (64)(65)(66)(67)(68), epilepsy (69,70) and autism (71)(72)(73)(74). Although PLP deficiency is thought to contribute to the respective human conditions (3,75,76), PLP-dependent processes have not yet been considered in the context of 7,8-DHF-induced effects.…”
Section: Discussionmentioning
confidence: 99%
“…Protein extracts were quantified with Pierce ™ BCA Protein Assay kit (ThermoFisher, 23225). Western blot was performed as described in (Guarino et al, 2022). Briefly, 30μg of protein lysate were suspended in Laemmli sample buffer (final concentration: 50 mM Tris-HCl, pH 6.8, 2.5 mM EDTA/Na, 2% SDS, 5% glycerol, 0.2 M dithiothreitol, 0.01% bromophenol blue), denatured for 5 min at 95°C, loaded onto a 12.5% polyacrylamide gel and then transferred onto nitrocellulose membrane.…”
Section: Western Blottingmentioning
confidence: 99%